Progressive neoliberalism vs. reactionary populism : una scelta di Hobson - Fraser, Nancy (Scenari, 2021)
The victory of Donald Trump has marked the deep crisis of a specific form of neoliberalism, namely the progressive neoliberalism. Inaugurated by the Bill Clinton’s presidency, progressive neoliberalism has been politically and culturally hegemonic till recently, especially in the United States. Also for this reason, the crisis of neoliberalism has assumed prevalently reactionary declinations. Thus, to contrast reactionary populism it is necessary to recover an authentic progressivism, by overcoming any compromise with neoliberalism.